A review on MnZn ferrites: Synthesis, characterization and applications. Issue 10 (July 2020) - Thakur, Preeti; Chahar, Deepika; Taneja, Shilpa; Bhalla, Nikhil; Thakur, Atul
Abstract: Researchers are taking great interest in the synthesis and characterization of MnZn ferrites due to their wide range of applications in many areas. MnZn ferrites are a class of soft magnetic materials that have very good electrical, magnetic and optical properties. The properties of MnZn ferrites include high value of resistivity, permeability, permittivity, saturation magnetization, low power losses and coercivity. The above mentioned advantageous features of MnZn ferrites make them suitable for the use in various applications. In biomedical field these ferrites are used for cancer treatment and MRI. MnZn ferrites are also used in electronic applications for making transformers, transducers and inductors. These ferrites are also used in magnetic fluids, sensors and biosensors. MnZn ferrite is highly useful material for several electrical and electronic applications. It finds applications in almost every household appliances like mobile charger, LED bulb, TV, refrigerator, juicer mixer, washing machine, iron, microwave oven, mobile, laptop, desktop, printer and so on. Therefore, the present review focuses on different techniques for synthesis of MnZn ferrites in literature, their characterization tools, effect of doping on the properties of MnZn ferrite and finally we will discuss about their applications.